2441 INTERLEUKIN-1B AND CYCLOOXYGENASE-2 PROINFLAMMATION ANALYSIS AND IN SILICO DOCKING NUCLEAR FACTOR KAPPA B ON ENDOMETRIOSIS CELL CULTURE GIVEN HEPTYL GALLATE AND OCTYL GALLATE TREATMENT - BUSTAMI, ARLENI; SULISTYA UTAMI, FAJAR; BUDIARTI, RAHMI; WIBOWO, HERI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The aim of this study is to analyze the effect of octyl gallate and heptyl gallate toward the regulation of interleukin-1β and cyclooxygenase (COX)-2 proinflammatory factor on endometriosis cell culture and analyze its activity toward nuclear factor kappa B (NFkB) target protein through in silico docking technique. Methods: In vitro study was performed on endometriosis cells cultured treated with two dosages each of heptyl and octyl gallate (51.2 μg/mL and 102.4 μg/mL) for 48 h, then followed by 10 ng/mL lipopolysaccharides (LPS) induction for 24 h. The positive control group was treated by LPS induced and the negative control was treated without LPS. Inflammation regulation was evaluated with enzyme-linked immunosorbent assay technique and in silico docking analyzed using bioinformatics technique. Results: Molecular docking analysis with gallic acid and their derivatives showed that more stable affinity and stronger binding found on octyl gallate than heptyl gallate and gallic acid at the active site of NFkB. Conclusions: Based on this study results, octyl gallate and heptyl gallate were proven to be able to reduce COX-2 proinflammatory factor through NFkB pathway as an inflammatory regulator; thus, it has the potential to be developed as a therapy for endometriosis.